Strategy To Increase The Competitiveness Of Umkm In The Tourism And Creative Economy Sector Of Samosir Regency With Go-Digital And Transformational Leadership - Ekana Nainggolan, Lora; Triapnita Nainggolan, Nana; Lie, Darwin (International Journal of Science, Technology & Management, 2023)
MSMEs in the tourism sector play an important role in business development and continue to contribute to economic strength and social development in various countries, one of which is Indonesia, and support each other and contribute to generating foreign exchange for the country. The euphoria of the world community has caused tourism visits to increase, especially after Indonesia officially hosted World Tourism Day or World Tourism Day 2022, which had the impact of becoming increasingly well-known to the tourism sector, especially Samosir Regency. This research took a population of 462 MSMEs in Samosir Regency with a sampling technique, namely cluster random sampling with a sample size of 150 MSMEs in 2 Districts of Samosir Regency. Data sources include secondary data originating from relevant agencies and primary data directly from business actors. Data collection techniques use interview documentation and questionnaires. The research results showed that the influence of Go-digitalization and transformational leadership was positive and significant on competitive strategies for MSME actors in the Tourism and Creative Economy sectors of Samosir Regency. The development of digital technology is increasingly rapid, especially after the pandemic disaster. This also encourages community actors to shop online. It's no wonder that electronic trading platforms are selling well as people's choice for shopping and transactions. MSME digital acceleration is carried out to build competitiveness so that MSMEs can be stronger. Transformational leadership is the process of mobilizing all one's abilities to influence, move, direct other people. Transformational leadership is a process of mobilizing all one's abilities to influence, move and direct other people. The suggestion from this research is government support to encourage and provide assistance to business actors so they are able to compete with other tourism industries. One form of support is for the government to provide space for learning to realize technological literacy through outreach and training to business actors. Then we need to utilize new marketing strategies, actively producing goods that consumers can buy directly for the types of products that are currently on the rise during the pandemic.